Sefl-Efficacy Training to Improve Students’ Self-Concept - Rizki Maghfiroh; Purwati Purwati; Hijrah Eko Putro (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This research aims to determine the effect of self-efficacy training on improvingthe self-concept of seventh grade students of SMP Plus Ihya’ul Ulum Muntilan.This research is true experimental design research with pretest-posttest controlgroup design. Research subject were selected using simple random sampling. Thesamples taken were 22 students consisting of 11 students as the experimental group and 11 students as the control group. The method of data collection is done by using a self-concept questionnaire. The analysis prerequisite test consists of a normality test and a homogenity test. Data analysis used One Way Anova Parametric Statistical analysiswith the help of SPSS version 25.The result showed that self-efficacy training had an effect on increasing students’self-concept. This is evidenced by the result of the One Way Anova Parametric Statisticstest with a probability value of sig. (2-tailed) 0,004 < 0,05. Based on the result of the analysis and discussion, there is a difference in the average score of the student self-concept questionnaire between the experimental group by 12% and the control group by 4%. The result of the study can be concluded that there is an effect of self-efficacytraining to improve students’ self-concept.